Comorbidities Before and After the Diagnosis of Rheumatoid Arthritis: A Matched Longitudinal Study. Issue 11 (26th October 2020) - Tatangelo, Mark R.; Tomlinson, George; Keystone, Edward; Paterson, J. Michael; Bansback, Nick; Bombardier, Claire
Abstract : Objective: To determine the contribution of rheumatoid arthritis (RA) to conditions and medical events. A secondary objective is to quantify this association before and after the introduction of biologic medications. Methods: All data were collected as health administrative data in Ontario, Canada. Patients with RA (n = 136 678) matched 1:1 to a pool of possible controls without RA from 1995 to 2016. The study was a retrospective longitudinal observational administrative data‐based cohort study with cases (RA) and controls (two non‐RA comparator groups). The main exposure was new‐onset RA identified by a validated diagnosis algorithm. The secondary exposure was the calendar year, which provided a natural experiment to compare years in which biologics were unavailable (pre‐2001) to increasing utilization over time. The main outcomes were counts of 27 Johns Hopkins Expanded Diagnostic Cluster Comorbid Conditions. Outcomes were reported as counts and percentage differences between cases and matched controls. Results: Patients experienced increases in conditions and medical events up to 5 years before RA disease incidence—4.9 conditions per patient‐year compared with 4.6 conditions per patient‐year in matched controls. Comorbidities increased to 8.7 conditions per patient‐year in the year of RA incidence but were lower in the years after diagnosis—6.9 conditions per patient‐year at 5 years postdiagnosis. Conclusion: This study reframes the clinical manifestations of RA with detailed data on the marginal contribution of RA to conditions and medical events. These results show that a large portion of disease burden is due to the indirect effects of RA.